2021
DOI: 10.3390/app11041736
|View full text |Cite
|
Sign up to set email alerts
|

Structural Identification and Coagulation Effect of Flammulina velutipes Polysaccharides

Abstract: Two polysaccharides were isolated successfully from Flammulina velutipes and identified as CHFVP-1 (24.44 kDa) and CHFVP-2 (1497 kDa). Based on the results of Fourier transform-infrared spectroscopy (FT-IR), gas chromatography (GC), gas chromatography–mass spectrometry (GC–MS), and nuclear magnetic resonance (NMR) spectroscopy regarding the structure of CHFVP-1 and CHFVP-2, CHFVP-1 was constructed with the backbone of→6)-α-D-Galp-(1→ and the branch of Galp by an →3,6)-α-D-Manp-(1→attached with T-β-D-Glcp or t-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…The yields of FVP and FFVP were 8.65 and 9.44%, respectively, and MW of 15,961 and 15,702 Da (Figure 1), respectively. Besides, the MW/MN (Weight-average Molecular Weight/Number-average Molecular Weight) of FVP and FFVP were 1.20 and 1.09 (Supplementary Figure 2), respectively, which was similar to a previous report (1.042) (16). A previous study has also reported that the contents and MW of tea polysaccharides, compared with the unfermented group, were, respectively, increased and decreased after fermentation treatment, and the biological capacities of fermented fractions were also better than unfermented ones (22).…”
Section: Results and Discussion Physicochemical Analysis Of Fvp And Ffvpsupporting
confidence: 90%
See 1 more Smart Citation
“…The yields of FVP and FFVP were 8.65 and 9.44%, respectively, and MW of 15,961 and 15,702 Da (Figure 1), respectively. Besides, the MW/MN (Weight-average Molecular Weight/Number-average Molecular Weight) of FVP and FFVP were 1.20 and 1.09 (Supplementary Figure 2), respectively, which was similar to a previous report (1.042) (16). A previous study has also reported that the contents and MW of tea polysaccharides, compared with the unfermented group, were, respectively, increased and decreased after fermentation treatment, and the biological capacities of fermented fractions were also better than unfermented ones (22).…”
Section: Results and Discussion Physicochemical Analysis Of Fvp And Ffvpsupporting
confidence: 90%
“…The residues were then extracted with distilled water, and the supernatant was filtered, combined, and concentrated. The crude polysaccharides were then precipitated by adding ethanol and washed successively with anhydrous ethanol, acetone, and petroleum ether ( 16 ). The extracted crude FVP was then harvested after deproteinization with Sevag solution (chloroform: butylalcohol = 5:1) and fractionated through diethylaminoethyl (DEAE)–Sepharose fast flow column (elution conditions: distilled water and 0.05, 0.1, 0.2, 0.3, and 0.5 mol/L NaCl gradient solutions) ( 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Earlier experiments of our group found that F. velutipes polysaccharides were non-toxic and could promote intestinal motility and improve constipation in rats (11). Liang obtained two polysaccharides CHFVP-1 (24.44 kDa) and CHFVP-2 (1,497 kDa) from F. velutipes and found that CHFVP-1 had procoagulant activity in vitro (12). A review of the literature shows that F. velutipes polysaccharides can modulate the intestinal microbiota of healthy mice and has potential immunomodulatory abilities (13,14).…”
Section: Introductionmentioning
confidence: 96%
“…The polysaccharides from fruiting bodies of P. placentodes were extracted and purified according to our previous method (Liang et al, 2021) with some modifications. First, the fruiting bodies were extracted with 70% ethanol, and then the residues were slightly boiled twice with water for 4 h. The extracting solution was concentrated to a density of 1.1 in vacuum at 55 °C.…”
Section: Extraction and Purification Of Polysaccharides From P Placentodesmentioning
confidence: 99%
“…Normal saline was blank control (BC). Referring to our previous experimental method (Liang et al, 2021), according to the operation instructions of APTT, PT, and TT assay kits, the APTT, TT, and PT values were determined on a RAC-030 automatic coagulation analyzer (Shenzhen Leidu Life Science Co., Ltd. Guangdong, China).…”
Section: Anticoagulant Activity and Statistical Analysismentioning
confidence: 99%